Translocation of 40 nm diameter nanowires through the intestinal epithelium of Daphnia magna. Issue 8 (13th September 2016) - Mattsson, Karin; Adolfsson, Karl; Ekvall, Mikael T.; Borgström, Magnus T.; Linse, Sara; Hansson, Lars-Anders; Cedervall, Tommy; Prinz, Christelle N.
Abstract: Nanowires (NWs) have unique electrical and optical properties of value for many applications including lighting, sensing, and energy harnessing. Consumer products containing NWs increase the risk of NWs being released in the environment, especially into aquatic ecosystems through sewage systems. Daphnia magna is a common, cosmopolitan freshwater organism sensitive to toxicity tests and represents a likely entry point for nanoparticles into food webs of aquatic ecosystems. Here we have evaluated the effect of NW diameter on the gut penetrance of NWs in Daphnia magna . The animals were exposed to NWs of two diameters (40 and 80 nm) and similar length (3.6 and 3.8 μm, respectively) suspended in water. In order to locate the NWs in Daphnia, the NWs were designed to comprise one inherently fluorescent segment of gallium indium phosphide (GaInP) flanked by a gallium phosphide (GaP) segment. Daphnia mortality was assessed directly after 24 h of exposure and 7 days after exposure. Translocation of NWs across the intestinal epithelium was investigated using confocal fluorescence microscopy directly after 24 h of exposure and was observed in 89% of Daphnia exposed to 40 nm NWs and in 11% of Daphnia exposed to 80 nm NWs. A high degree of fragmentation was observed for NWs of both diameters after ingestion by the Daphnia, although 40 nm NWs were fragmented to a greater extent, which could possibly facilitate translocation across the intestinal epithelium. Our results show that the feeding behavior of animals may enhance the ability of NWs to penetrate biological barriers and that penetrance is governed by the NW diameter.